Sintering mechanics of binder jet 3D printed ceramics treated with a reactive binder. Issue 6 (June 2023) - Grant, Lynnora O.; Higgs, C. Fred; Cordero, Zachary C.
Abstract: Reactive binders mitigate distortion during sintering of binder jet 3D printed components by precipitating a solid phase that reinforces interparticle contacts. The present work combines experiments with micromechanical modeling to clarify how aqueous titanium bis-ammonium lactato dihydroxide (TALH), a reactive binder, affects creep and densification during sintering of binder jet printed TiO2 . TALH treatment of as-printed material results in a nanocrystalline TiO2 overlayer that coats the micron-scale particles. At sintering temperatures, this overlayer is consumed via grain growth such that the structures of the TALH-treated and neat materials appear nearly identical. Creep rates are slower in the TALH-treated material than in the as-printed TiO2, but creep in the treated material is faster when compared at equivalent relative density. TALH-treated and neat TiO2 both exhibit diffusional creep, with stress exponents near unity and activation energies of ∼400 kJ/mol. Models of structural evolution in sintering powder aggregates show that the dominant effect of TALH on the sintering mechanics is to increase the interparticle contact size, while the coordination number remains essentially unchanged. These insights are used to develop generalized guidelines for designing reactive binders to mitigate creep, quantitatively highlighting the benefits of a high solid yield from binder decomposition.